2012
DOI: 10.1017/s0033291712001912
|View full text |Cite
|
Sign up to set email alerts
|

Prospective predictors of adolescent suicidality: 6-month post-hospitalization follow-up

Abstract: Background The aim of this study was to examine prospective predictors of suicide events, defined as suicide attempts or emergency interventions to reduce suicide risk, in 119 adolescents admitted to an in-patient psychiatric unit for suicidal behaviors and followed naturalistically for 6 months. Method Structured diagnostic interviews and self-report instruments were administered to adolescent participants and their parent(s) to assess demographic variables, history of suicidal behavior, psychiatric disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
3
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 51 publications
10
110
3
5
Order By: Relevance
“…These findings are also in line with previous research [51,52]. Given the fact that one of the strongest predictors of completed suicide or further SAs has been found to be a previous SA [53,54] and that the D-BPP prospectively predicts adolescent SAs [55], the group identified may be at particular risk of future suicidal behavior and even suicide.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are also in line with previous research [51,52]. Given the fact that one of the strongest predictors of completed suicide or further SAs has been found to be a previous SA [53,54] and that the D-BPP prospectively predicts adolescent SAs [55], the group identified may be at particular risk of future suicidal behavior and even suicide.…”
Section: Discussionsupporting
confidence: 90%
“…However, our understanding of the role of affect intensity in relation to adolescent risk for suicide is limited. This is a notable gap in the literature, given the importance of affect, particularly strongly experienced affect, in terms of suicide risk among adults (e.g., Lynch et al 2004) and adolescents (e.g., Yen et al 2013). Importantly, findings from studies conducted with youth are mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the present study examined the relation between adolescent risk for suicide and affect intensity using the AIR-Y. In light of past findings suggesting a unique role of PA in risk for suicide (Hirsch et al 2007;Yen et al 2013), it was hypothesized that in the current cross-sectional study PA would be uniquely associated with suicide risk among treatment-seeking adolescents. Second, given cross-sectional data linking NI (without reference to NR) to risk for suicide ), we predicted NI, but not NR, would be uniquely associated with risk for suicide.…”
Section: Introductionmentioning
confidence: 98%
“…In particular, more research is warranted to determine whether the effect of worries on suicide attempts is independent of psychopathology, especially depression severity and/or hopelessness, two strong proximal factors for suicide attempts and relapse [34,47,48]. This study showed that the onset of stressful life events affected the level of worries among adolescents.…”
Section: Research and Clinical Implicationsmentioning
confidence: 92%